Nano-precipitation and carrier optimization synergistically yielding high-performance n-type Bi2Te3 thermoelectrics. (July 2021) - Yen, Wan-Ting; Huang, Hsin-Ching; Wang, Kuang-Kuo; Wu, Hsin-Jay
Abstract: The bismuth-tellurides have never ceased as the best candidates for thermoelectric (TE) coolers since the beginning of manufactures in the 1960s. As the years passed, the effort in boosting their performance continues abreast of breakthroughs in the conversion efficiencies with the occasional setbacks from the n -type alloys. Herein, a synergistic approach combining the phase diagram engineering and the carrier optimization overcomes the long-existing obstacle, eliciting an outperforming n -type Ag–Bi2 Te3 . The Ag0.03 Bi2 Te2.97 alloy attains a high figure-of-merit zT  = 1.4 at 363 K and a superior averaged zT ave  = 1.1 within 300 K–500 K. The phase diagram pinpoints a high- zT zone whose boundary coincides with the maximal Ag solubility. A close-up upon the best-performing Ag0.03 Bi2 Te2.97 reveals the presence of Ag2 Te nano-precipitates, explaining its low-lying κ L alongside the remarkable enhancement in its power factor PF  = S 2 ρ −1 . The avenue paved by the thermodynamic route essentially revives the TE research field, in which more potential candidates are awaiting further discovery. Graphical abstract: Image 1 Highlights: Phase diagram engineering elicits high performance TE materials. Carrier optimization is achieved in the Ag-incorporated Bi2 Te3 . Synergistically approaches lead to the enhanced σ and reduced κ L . A peak zT  = 1.4 at 363 K is obtained in n -type Ag–Bi2 Te3 . A high averaged zT ave  = 1.1 within 300 K–500 K is attained in n -type Ag–Bi2 Te3 .